Preparation method of graphene reinforced porous magnesium-based composite material
After surface treatment of graphene and mixing with magnesium alloy powder, a graphene-enhanced porous magnesium-based composite material is prepared by selective laser melting forming technology, which solves the problem of poor wetting between graphene and magnesium matrix, and significantly improves the mechanical properties and microhardness of the material.
Patent Information
- Application Number
- CN202411539757.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-04
AI Technical Summary
In the prior art, the wettability between graphene and magnesium matrix is poor, which makes it difficult for graphene to disperse uniformly in magnesium alloys, affecting the mechanical properties of the composite material.
Modified graphene was formed by adding graphene to a benign organic solvent solution containing 1,6-hexadipisocyanate for surface treatment and reacting under the action of an organic tin catalyst. Then, the modified graphene was mixed with the magnesium alloy powder, and the graphene-reinforced porous magnesium-based composite material was prepared by selective laser melt forming technology.
The dispersion uniformity of graphene in the magnesium matrix is improved, the interfacial bonding performance between graphene and magnesium matrix is enhanced, the mechanical properties of the composite material are improved, and the microhardness of the material is significantly improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal-based composite materials and relates to a magnesium-based composite material, and in particular to a method for preparing a graphene-reinforced porous magnesium-based composite material. Background Art
[0002] Metal fiber porous material is a composite structural functional material, whose internal structure is connected by metal fibers staggered and overlapped to form a three-dimensional mesh porous structure, with high-precision, fully connected pores, pore diameters as low as 10μm, porosity as high as 98%, and large specific surface area. The good basic properties and unique functional characteristics of metal porous materials have attracted widespread attention and have been applied and developed in many fields.
[0003] Among them, the characteristics of porous magnesium alloys mainly include light weight and high strength, excellent energy absorption capacity, good thermal conductivity and sound insulation, and adjustable pore structure. Its low density significantly reduces the weight of the material while maintaining high strength. The unique pore design not only enhances the energy absorption capacity of the material under impact load, but also improves the thermal conductivity efficiency and sound insulation effect. In addition, by adjusting the preparation process, the size and distribution of the pores can be precisely controlled to meet the specific needs of different application fields.
[0004] With the rapid development of aerospace technology, the demand for material performance is becoming increasingly stringent. Porous magnesium alloy materials with a single performance also face the challenge of not being able to meet all practical needs. Graphene, with its excellent mechanical properties (such as high strength and high toughness), excellent electrical and thermal conductivity, and unique two-dimensional structure, provides the possibility of improving the comprehensive performance of magnesium alloys. Introducing graphene as a reinforcing phase into magnesium alloys can significantly improve the mechanical properties of magnesium alloys, including improving strength, hardness and wear resistance, and may also enhance its electrical and thermal conductivity. As an emerging material, graphene / magnesium alloy composites have shown great application potential in aerospace, automobile manufacturing, electronic information and other fields. Therefore, graphene / magnesium-based composites have become an important composite material.
[0005] In modified graphene, isocyanate is a common graphene treatment method to improve the stability of graphene, but 1,6-hexamethylene diisocyanate, as a specific substance of isocyanate, has a specific chemical structure that allows it to interact more strongly with the functional groups on the surface of graphene, thereby forming a more stable chemical bond. The long chain structure of 1,6-hexamethylene diisocyanate may form a protective layer on the surface of graphene, effectively preventing erosion from the external environment, thereby improving the stability of graphene. 1,6-hexamethylene diisocyanate may interact with the electron cloud on the surface of graphene, changing the electronic structure of graphene and making it more stable.
[0006] CN117286388A discloses a high volume graphene reinforced magnesium-based composite material and a preparation method thereof, which is obtained by molding a composite melt containing a magnesium matrix, magnesium oxide nanoparticles and graphene. CN110904373A discloses a deep supercooling preparation method of a graphene-enhanced magnesium-based composite material, which is to ball-mill graphene and magnesium alloy powder and put them into a smelting furnace for heating and heat preservation, and then naturally cool them, and then peel off the quartz crucible and the boron trioxide, thereby obtaining a solid graphene-enhanced magnesium-based composite material. CN111996410A relates to a preparation method of a graphene-enhanced magnesium-based composite material, which comprises mixing a reinforcement, a magnesium matrix and a liquid compatibilizer to obtain a suspension; spray drying the obtained suspension to obtain a dry powder; molding the obtained dry powder to obtain a block blank; melting and mixing the block blank and a magnesium alloy blank, and casting to obtain a graphene-enhanced magnesium-based composite material.
[0007] The problems with the above methods are: the modified graphene has poor stability and poor wettability between graphene and the magnesium matrix, which makes it difficult for graphene to be evenly dispersed in the magnesium alloy, thereby affecting the mechanical properties of the composite material. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing a graphene-reinforced porous magnesium-based composite material, so as to overcome the problems of poor wettability between graphene and a magnesium matrix and difficulty in forming pores in preparing the porous magnesium-based composite material.
[0009] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a graphene-reinforced porous magnesium-based composite material comprises the following steps: 1) adding graphene to a benign organic solvent solution containing 1,6-hexamethylene diisocyanate and performing surface treatment under the action of an organic tin catalyst to promote an effective reaction between graphene and 1,6-hexamethylene diisocyanate; 2) Using potassium oxalate as a reducing agent, the surface-treated graphene is subjected to a reduction reaction to obtain modified graphene; 3) Placing the modified graphene in a closed system and introducing the required gas, so that the surface of the modified graphene fully adsorbs the gas under the action of the external gas pressure; 4) dispersing the modified graphene adsorbed with gas in N,N-dimethylacetamide, then adding magnesium alloy powder, ball milling with a ball mill, and drying to prepare a modified graphene / magnesium alloy powder mixed powder; 5) Under the protection of an inert environment, the modified graphene / magnesium alloy powder mixture is subjected to selective laser melting to prepare a graphene-reinforced porous magnesium-based composite material.
[0010] The present invention utilizes the advantage of large specific surface area of graphene to adsorb gas on the graphene surface, and then mixes the gas-adsorbed graphene with magnesium alloy powder for selective laser melting forming. During the forming process, the gas adsorbed on the graphene surface will form bubbles, and since the solidification speed of the magnesium matrix after melting is fast, the bubbles will be solidified inside the alloy, thereby preparing a graphene-reinforced porous magnesium-based composite material.
[0011] In the above-mentioned preparation method of the present invention, the selective laser melting forming is to use a laser with a power of 400 to 500W to scan the modified graphene / magnesium alloy powder mixture.
[0012] Preferably, the modified graphene / magnesium alloy powder mixture is laid to a thickness of 20 to 100 μm and scanned layer by layer for forming.
[0013] More preferably, the scanning speed is 5 to 20 m / s.
[0014] Specifically, in the process of surface treatment of graphene in the present invention, the mass ratio of graphene to 1,6-hexamethylene diisocyanate is 1:5-20.
[0015] More specifically, in the present invention, the 1,6-hexamethylene diisocyanate is formulated into a benign organic solvent solution with a concentration of 5 to 30 wt%.
[0016] More preferably, the benign organic solvent may be any one of butanone, acetone, and ether.
[0017] Specifically, the organotin catalyst may be any one of dibutyltin dilaurate, stannous octoate, and dibutyltin diacetate, and the mass ratio of the organotin catalyst to the graphene is 0.1% to 2%, preferably 0.9%.
[0018] Specifically, the surface treatment process of graphene in the present invention can be carried out under ultrasonic stirring conditions, and the ultrasonic stirring time is preferably 0.5 to 1.5 hours.
[0019] Furthermore, in the present invention, in the reduction reaction of the surface-treated graphene using potassium oxalate, the mass ratio of the potassium oxalate to the surface-treated graphene is 0.1 to 10:10, preferably 1 to 6:10.
[0020] Furthermore, in the present invention, the potassium oxalate is prepared into a potassium oxalate aqueous solution with a concentration of 6 to 25 wt %.
[0021] Furthermore, the reduction reaction time of the present invention is 1 to 1.5 hours.
[0022] Furthermore, the modified graphene obtained by the reduction reaction is ultrasonically cleaned and then vacuum dried at 60-80°C.
[0023] Furthermore, the gas adsorption of the modified graphene in a closed system is carried out under the closed system conditions of a temperature of 25-35° C. and an external gas pressure of 400-500 KPa.
[0024] Furthermore, the gas is an inert gas, preferably nitrogen or argon.
[0025] Furthermore, the flow rate of the introduced gas is preferably 10 to 30 L / h.
[0026] Furthermore, the gas adsorption time is preferably 1 to 2 hours.
[0027] Furthermore, in the above preparation method of the present invention, the modified graphene that adsorbs gas, N,N-dimethylacetamide, and magnesium alloy powder are mixed in a mass ratio of 1:4 to 6:9 to 10 and ball milled.
[0028] Furthermore, the ball milling is specifically carried out at a ball-to-material ratio of 6 to 10:1 in a ball mill at a rotation speed of 200 to 230 rpm for 1 to 3 hours.
[0029] Furthermore, the material obtained by ball milling is vacuum dried at 40-60° C. for 1-3 hours to prepare a modified graphene / magnesium alloy powder mixed powder.
[0030] Compared with the prior art, the present invention has the following beneficial effects: 1. In the preparation method of the graphene-enhanced porous magnesium-based composite material of the present invention, 1,6-hexamethylene diisocyanate is used to surface treat graphene, which improves the stability of graphene compared with other types of isocyanates. Compared with diisocyanate substances, 1,6-hexamethylene diisocyanate is a specific diisocyanate, and its carbon chain is longer, and it has better flexibility and steric hindrance effect, which enables it to form a more stable chemical bond when reacting with graphene. In addition, the longer carbon chain can also provide more reaction sites, increase the contact area with the graphene surface, and further improve the modification effect. In the presence of an organotin catalyst, the isocyanate group of 1,6-hexamethylene diisocyanate reacts with the functional group on the graphene surface to form a stable chemical bond such as a carbamate bond or a urea bond. These chemical bonds not only improve the dispersibility of graphene, but also enhance its compatibility with magnesium alloy powder, providing favorable conditions for subsequent ball milling mixing and laser melting forming. At the same time, the use of N,N-dimethylacetamide effectively improves the dispersion of graphene in the ball milling process of graphene and magnesium alloy powder.
[0031] 2. The method of the present invention is used to prepare a graphene-reinforced porous magnesium-based composite material, which solves the problem of poor wettability between graphene and the magnesium matrix, improves the dispersion uniformity of graphene in the magnesium matrix, overcomes the agglomeration problem of graphene, improves the interface bonding performance between graphene and the magnesium matrix, and improves the mechanical properties of the composite material.
[0032] 3. At the same time, the present invention utilizes the two-dimensional crystal structure of graphene and its large surface area and pore structure, which can fully contact with the gas, and combines it with 3D printing technology to prepare a porous metal composite material with rich and uniform internal pore structure. DETAILED DESCRIPTION
[0033] The specific embodiments of the present invention are further described below in conjunction with examples. The following examples are only used to more clearly illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Various changes, modifications, substitutions and variations made to these embodiments by those of ordinary skill in the art without departing from the principles and purpose of the present invention should all be included in the scope of protection of the present invention.
[0034] The magnesium alloy powder used in the embodiment of the present invention is a magnesium alloy with the grade of AZ91. Example 1
[0035] The preparation method of the graphene-reinforced porous magnesium-based composite material of this embodiment is as follows.
[0036] 480 g of 1,6-hexamethylene diisocyanate was dissolved in 4.09 kg of butanone to prepare a butanone solution containing 10.5 wt % of 1,6-hexamethylene diisocyanate.
[0037] 96 g of graphene and 0.864 g of dibutyltin dilaurate catalyst were added to the above-mentioned 1,6-hexanediisocyanate in butanone solution, and the mixture was treated with ultrasonic stirring for 1 h. The graphene treated with 1,6-hexanediisocyanate was added to 192 mL of 10 wt% potassium oxalate solution and treated with ultrasonic stirring for 1.5 h. The reduced product was filtered out, ultrasonically cleaned with acetone, placed in an oven, and dried at 60 ° C for 3 h to obtain modified graphene.
[0038] The modified graphene was placed in a closed system at 25° C., argon gas was introduced at a gas flow rate of 10 L / h, and gas adsorption was performed in the closed system with an external gas pressure of 400 KPa for 1 h.
[0039] The modified graphene adsorbing nitrogen was ultrasonically dispersed in 480g of N,N-dimethylacetamide, and 960g of magnesium alloy powder was added to the ball mill at a ball-to-material ratio of 8:1, and the ball mill was milled at a speed of 200 rpm for 1 hour. The material was taken out and vacuum dried at 40°C for 1 hour to obtain a modified graphene / magnesium alloy powder mixed powder.
[0040] A modified graphene / magnesium alloy powder mixture with a thickness of 20 μm was continuously laid on the working cylinder of the selective laser melting forming equipment. Under the protection of Ar gas, a 400 W laser was used to scan the laid mixed powder layer by layer at a scanning speed of 8 m / s. The adsorbed gas was overflowed through laser heating, and finally a graphene-reinforced porous magnesium-based composite material was deposited layer by layer.
[0041] Hardness is the main index to measure the comprehensive performance of materials. The microhardness of the graphene-reinforced porous magnesium-based composite material prepared above was tested by HVS-1000 microhardness tester, and the result was 123Hv.
[0042] At the same time, according to the above-mentioned selective laser melting forming method, magnesium alloy material was directly prepared by 3D printing using magnesium alloy powder, and its microhardness was tested to be 96Hv.
[0043] Under the same preparation method, the microhardness of graphene-reinforced porous magnesium-based composite materials is 28.125% higher than that of magnesium alloy materials. Example 2
[0044] The preparation method of the graphene-reinforced porous magnesium-based composite material of this embodiment is as follows.
[0045] 2.42 kg of 1,6-hexamethylene diisocyanate was dissolved in 10 kg of butanone to prepare a butanone solution containing 19.5 wt % of 1,6-hexamethylene diisocyanate.
[0046] 242 g of graphene and 2.178 g of dibutyltin dilaurate catalyst were added to the above 1,6-hexanediisocyanate in butanone solution, and the mixture was treated with ultrasonic stirring for 1 h. The graphene treated with 1,6-hexanediisocyanate was added to 645.30 mL of 15 wt% potassium oxalate solution, and the mixture was reduced with ultrasonic stirring for 1.5 h. The reduced product was filtered out, ultrasonically cleaned with acetone, placed in an oven, and dried at 70 ° C for 3 h to obtain modified graphene.
[0047] The modified graphene was placed in a closed system at 25°C, nitrogen was introduced at a gas flow rate of 20 L / h, and gas adsorption was performed under an external gas pressure of 450 KPa for 1.5 h.
[0048] The modified graphene adsorbing nitrogen was ultrasonically dispersed in 1.41 kg N,N-dimethylacetamide, and 2.42 kg magnesium alloy powder was added to the ball mill at a ball-to-material ratio of 9:1, and the ball mill was milled at a speed of 210 rpm for 2 h. The material was taken out and vacuum dried at 50°C for 2 h to obtain a modified graphene / magnesium alloy powder mixed powder.
[0049] A modified graphene / magnesium alloy powder mixture with a thickness of 40 μm was continuously laid on the working cylinder of the selective laser melting forming equipment. Under the protection of Ar gas, a 450W laser was used to scan the laid mixed powder layer by layer at a scanning speed of 10 m / s. The adsorbed gas was overflowed by laser heating, and finally a graphene-reinforced porous magnesium-based composite material was deposited layer by layer.
[0050] The microhardness of the graphene-enhanced porous magnesium-based composite material prepared above was tested to be 127Hv, while the microhardness of the magnesium alloy material prepared directly using magnesium alloy powder according to the selective laser melting forming method was 98Hv. The microhardness of the graphene-enhanced porous magnesium-based composite material is 29.59% higher than that of the magnesium alloy material. Example 3
[0051] The preparation method of the graphene-reinforced porous magnesium-based composite material of this embodiment is as follows.
[0052] 3.1667 kg of 1,6-hexamethylene diisocyanate was dissolved in 9.2 kg of butanone to prepare a butanone solution containing 25.6 wt % of 1,6-hexamethylene diisocyanate.
[0053] 158.335 g of graphene and 1.425 g of dibutyltin dilaurate catalyst were added to the above-mentioned 1,6-hexanediisocyanate in butanone solution, and the mixture was treated with ultrasonic stirring for 1.5 h. The graphene treated with 1,6-hexanediisocyanate was added to 380 mL of 25 wt% potassium oxalate solution, and the mixture was reduced with ultrasonic stirring for 1.5 h. The reduced product was filtered out, ultrasonically cleaned with acetone, placed in an oven, and dried at 80 ° C for 3 h to obtain modified graphene.
[0054] The modified graphene was placed in a closed system at 35° C., nitrogen was introduced at a gas flow rate of 30 L / h, and gas adsorption was performed under an external gas pressure of 500 KPa for 2 h.
[0055] The modified graphene adsorbing nitrogen was ultrasonically dispersed in 791.5 g of N,N-dimethylacetamide, and 1.583 kg of magnesium alloy powder was added to the ball mill at a ball-to-material ratio of 10:1, and the ball mill was milled at a speed of 230 rpm for 3 h. The material was taken out and vacuum dried at 60° C. for 3 h to obtain a modified graphene / magnesium alloy powder mixed powder.
[0056] A modified graphene / magnesium alloy powder mixture with a thickness of 80 μm was continuously laid on the working cylinder of the selective laser melting forming equipment. Under the protection of Ar gas, a 500 W laser was used to scan the laid mixed powder layer by layer at a scanning speed of 20 m / s. The adsorbed gas was overflowed through laser heating, and finally a graphene-reinforced porous magnesium-based composite material was deposited layer by layer.
[0057] The microhardness of the graphene-enhanced porous magnesium-based composite material prepared above was tested to be 130Hv, while the microhardness of the magnesium alloy material prepared directly using magnesium alloy powder according to the selective laser melting forming method was 103Hv. The microhardness of the graphene-enhanced porous magnesium-based composite material is 26.21% higher than that of the magnesium alloy material.
Claims
1. A method for preparing a graphene-enhanced porous magnesium-based composite material, characterized in that: The preparation method comprises the following steps: 1) adding graphene to a benign organic solvent solution containing 1,6-hexamethylene diisocyanate and performing surface treatment under the action of an organic tin catalyst to promote an effective reaction between graphene and 1,6-hexamethylene diisocyanate; 2) Using potassium oxalate as a reducing agent, the surface-treated graphene is subjected to a reduction reaction to obtain modified graphene; 3) placing the modified graphene in a closed system, introducing gas, and allowing the surface of the modified graphene to fully adsorb the gas under the action of the external gas pressure; 4) dispersing the gas-adsorbed modified graphene in N,N-dimethylacetamide, adding magnesium alloy powder, ball milling, and drying to obtain a modified graphene / magnesium alloy powder mixed powder; 5) Selectively laser melting the modified graphene / magnesium alloy powder mixture in an inert environment to form a graphene-reinforced porous magnesium-based composite material.
2. The method for preparing the graphene-enhanced porous magnesium-based composite material according to claim 1, characterized in that: In the step 1), the mass ratio of graphene to hexamethylene diisocyanate is 1:5-20.
3. The method for preparing the graphene-enhanced porous magnesium-based composite material according to claim 1, characterized in that: The mass concentration of the benign organic solvent solution of 1,6-hexamethylene diisocyanate in step 1) is 5-30wt%, and the benign organic solvent is one of butanone, acetone and ether.
4. The method for preparing the graphene-enhanced porous magnesium-based composite material according to claim 1, characterized in that: In the step 1), the organotin catalyst is one of dibutyltin dilaurate, stannous octoate and dibutyltin diacetate, and the mass ratio of the organotin catalyst to the graphene is 0.1% to 2%.
5. The method for preparing the graphene-enhanced porous magnesium-based composite material according to claim 1, characterized in that: In the step 2), the mass ratio of potassium oxalate to the surface-treated graphene is 0.1 to 10:
10.
6. The method for preparing the graphene-enhanced porous magnesium-based composite material according to claim 1, characterized in that: In the step 2), the surface treated graphene is added to a 6-25wt% potassium oxalate solution and subjected to ultrasonic stirring reduction treatment for 1-1.5h.
7. The method for preparing the graphene-enhanced porous magnesium-based composite material according to claim 1, characterized in that: In the step 3), the modified graphene is adsorbed for 1 to 2 hours under the conditions of a closed system with a temperature of 25 to 35° C. and an external inert gas pressure of 400 to 500 KPa.
8. The method for preparing the graphene-enhanced porous magnesium-based composite material according to claim 1, characterized in that: The flow rate of the inert gas introduced in step 3) is 10 to 30 L / h.
9. The method for preparing the graphene-enhanced porous magnesium-based composite material according to claim 1, characterized in that: In the step 4), the mass ratio of the modified graphene for adsorbing gas, N,N-dimethylacetamide and magnesium alloy powder is 1:4-6:9-10.
10. The method for preparing the graphene-enhanced porous magnesium-based composite material according to claim 1, characterized in that: In the step 5), the selective laser melting forming is to use a laser with a power of 400 to 500 W to lay the modified graphene / magnesium alloy powder mixture into a thickness of 20 to 100 μm and perform layer-by-layer scanning forming at a scanning speed of 5 to 20 m / s.
Citation Information
Patent Citations
Deep supercooling preparation method of graphene reinforced magnesium-based composite material
CN110904373A
Graphene reinforced magnesium-based composite material as well as preparation method and application thereof
CN111996410A
High-volume-fraction graphene reinforced magnesium-based composite material and preparation method thereof
CN117286388A